Implementation of Regional Regulation Number 13 of 2011 concerning Retribution for Waste and Cleaning Services in Tualang District, Siak Regency - Sari, Dewi Komala; Arianto, Jumili; Hardian, Mirza (CV. Rayyan Dwi Bharata, 2024)
The policy of reimbursement of accommodation or hygiene services in Tualang district of the Siak district in its implementation is still not running optimally. As a result of an interview with the Chief of the Environmental Services at Tualang district of Siak, he noted that the implementation of the policy is still not running optimally due to several factors, namely the lack of facilities for the handling of garbage. The purpose of this research is to determine how the implementation of PERDA No. 13 Year 2011 on Retribution of Public Service and Sanitation in Tualang district of Siak. The method used is purposive sampling. Data collection techniques based on observations and interviews. According to the results of the research obtained, the Implementation of PERDA No. 13 of 2011 on Retribution of Public Service and Sanitation by the government of the district has been implemented even though it has not yet been fully implemented. In terms of delivery of services or infrastructure, governments still have to improve services and infrastructure.